Penerapan Buerger Allen Exercise untuk Meningkatkan Nilai Ankle Brachial Index (ABI) dalam Asuhan Keperawatan pada Pasien Diabetes Melitus Tipe II di Ruangan Interne Wanita Wing A RSUP Dr. M.Djamil Padang - Siska, Feby; Indri Ramadini; Efitra; Reni Susanti (Jurnal Kesehatan Cendikia Jenius, 2024)
Diabetes mellitus is a serious chronic disease that occurs when the pancreas cannot produce enough insulin. diabetes mellitus type II is a condition where blood sugar rises due to pancreatic beta cells producing less insulin and impaired insulin function or resistance. Therapy in patients with diabetes mellitus type II can be done with pharmacological and non-pharmacological therapies. One of the non-pharmacological therapies to increase the ankle brachial index value is Buerger Allen exercise therapy. This therapy aims to increase perfusion in the lower extremities, reduce pain, increase blood supply to the extremities and potentially cause the formation of new vascular structures so that it can help heal ulcers. The research design used descriptive observation in the form of a case report. The study was conducted in the female interne room Wing A of hospital Dr.M.Djamil Padang. The research time was April-May 2024, and the sample size was 2 participants. The results of the study in patient I showed an increase of 0.03, while in patient II there was an increase of 0.07, then it can be concluded that there is an effect of giving buerger allen exercise therapy on increasing ABI values in DM Type II patients. It is recommended that the hospital is expected to apply buerger allen exercise therapy to increase the value of the ankle brachial index in patients with diabetes mellitus type II.